FACTORS AFFECTING KNOWLEDGE SHARING OF ENGINEERS IN OIL AND GAS COMPANIES - Hadi Almher, Mustafa Ahmed; Thiruchelvam, Sivadass A/L; Abdal, Banan Badeel; Bte Jais, Juraifa; Aliyu, Muhammad Mukhtar (Center for Study and Journal Management FTI UMI, 2021)
Knowledge sharing among employees has been identified as one of the factors that contribute to improved job performance. Thus, this study examines the relationship between engineer’s perceived enjoyment, perceived status and subjective norm on their intention towards knowledge sharing in public oil and gas firms in Iraq. The study selects 240 engineers from oil and gas companies in Iraq to participate in the research. A questionnaire designed in a Likert scale format was used for the data collection. The data were analysed using descriptive statistical analysis and Correlation analysis. The results of the analysis show that there is a positive relation between engineer’s perceived enjoyment, perceived status and subjective norm on their intention towards knowledge sharing in public oil and gas firms in Iraq. The paper makes some recommendations on how to increase engineers’ perceived enjoyment, perceived status and subjective norm and eventually increase intention towards knowledge sharing.